2001
DOI: 10.1348/096317901167217
|View full text |Cite
|
Sign up to set email alerts
|

Testing reciprocal relationships between job characteristics and psychological well‐being: A cross‐lagged structural equation model

Abstract: This article describes a two‐wave panel study which was carried out to examine reciprocal relationships between job characteristics and work‐related psychological well‐being. Hypotheses were tested in a sample of 261 health care professionals using structural equation modelling (LISREL 8). Controlling for gender, age, and negative affectivity, the results primarily supported the hypothesis that Time 1 job characteristics influence Time 2 psychological well‐being. More specifically, Time 2 job satisfaction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
244
3
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(272 citation statements)
references
References 57 publications
17
244
3
8
Order By: Relevance
“…In that, consistent with the findings of De Jonge et al (2001), noted above, we found that none of these three outcomes at Time 1 predicted job control at Time 2.…”
Section: Job Controlsupporting
confidence: 92%
“…In that, consistent with the findings of De Jonge et al (2001), noted above, we found that none of these three outcomes at Time 1 predicted job control at Time 2.…”
Section: Job Controlsupporting
confidence: 92%
“…De Witte et al 2015). In sum, although the effects of work characteristics (de Lange et al 2004), unemployment (Griep et al 2014;McKee-Ryan et al 2005;Paul 2006;Paul and Moser 2009), and job insecurity (De Witte et al 2015) on health and well-being are causally predominant, several studies found evidence for reciprocal relationships (Christensen et al 2008;de Jonge et al 2001;Demerouti et al 2004;Herbig et al 2013;Hornung et al 2013;Paul 2006;Paul and Moser 2009;Varekamp and van Dijk 2010). Therefore, we warrant some caution when interpreting the discussed results in a causal way.…”
Section: Limitationsmentioning
confidence: 75%
“…Furthermore, a study by de Jonge et al, (2001) found weak evidence for the reverse effects of well-being on job characteristics, and only with regard to job demands. They did not find any evidence for reverse effects with regard to job control.…”
Section: Discussionmentioning
confidence: 97%